PENGARUH MEDIA CANTOL ROUDHOH TERHADAP KEMAMPUAN MENGENAL SUKU KATA DAN MENIRU HURUF PADA AUD (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2018)
ABSTRACTThis study aims to examine the influence of media cantol roudhoh the ability to know and imitate letter syllable. This study uses a design pattern quasi experimental research design non equivalent control group design. The collection of data through observation, the data processed by MANOVA test with SPSS 16.0. The results showed that (1) there was an effect on the ability of media cantol roudhoh recognize syllables, is evident from the test results of MANOVA showed Fhitung = 24.719 with sig. 0,000 less than 0.05. (2) the media's influence on the ability roudhoh hook imitate letters, evident from the test results of MANOVA showed Fhitung = 61.338 with sig. 0,000 less than 0.05. (3) the media's influence on the ability cantol roudhoh recognize syllables and letters imitate, is evident from the test results with calculations MANOVA Pillai's Trace, Wilk's lambda, Hotelling's Trace and Roy's Largest Root show Fhitung = 62 654 with sig. 0,000 less than 0.05. Because the three hypotheses stated